2019
DOI: 10.1089/heq.2019.0026
|View full text |Cite
|
Sign up to set email alerts
|

The Robert Wood Johnson Nurse Faculty Scholars Diversity and Inclusion Research

Abstract: The purpose of this research is to deepen the understanding of DEI training and show how scholars across the nation incorporated DEI leadership into academic roles. Faculty and administrators' experiential experience in diversity, equity, and inclusion (DEI) plays a role in the success or failure of DEI training. DEI training at institutes of higher learning should include metrics that examine our bias for invisible and overt support for DEI. Methods: Robert Wood Johnson Foundation Nurse Faculty Scholars (RWJF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Second, professional schools and programs would also benefit from the proposed framework of building a culture of IDEI assessment. Like EPPs, professional schools and programs around the country are struggling with how to effectively teach and assess IDEI education within their functional area [39][40][41]. For example, Johnson-Mallard et al's [40] research demonstrated that the following: Diversity among the nursing populations is critical, to reflect the society nurses serve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, professional schools and programs would also benefit from the proposed framework of building a culture of IDEI assessment. Like EPPs, professional schools and programs around the country are struggling with how to effectively teach and assess IDEI education within their functional area [39][40][41]. For example, Johnson-Mallard et al's [40] research demonstrated that the following: Diversity among the nursing populations is critical, to reflect the society nurses serve.…”
Section: Discussionmentioning
confidence: 99%
“…Like EPPs, professional schools and programs around the country are struggling with how to effectively teach and assess IDEI education within their functional area [39][40][41]. For example, Johnson-Mallard et al's [40] research demonstrated that the following: Diversity among the nursing populations is critical, to reflect the society nurses serve. In 2017, only 19.5% of all registered nurses in the United States identified as racial/ethnic minorities.…”
Section: Discussionmentioning
confidence: 99%
“…Caring for patients with COVID-19 in rural areas is a different challenge from cities. 23 The expression when knowing about the patient's condition makes the nurse sad and the guilt and fear of being infected causes different challenges. This is in line with this study that caregivers of chronic diseases expressed a variety of feelings and expressions from the first time they knew the diagnosis to continuing to care for at home and starting life adjustments.…”
Section: Discussionmentioning
confidence: 99%
“…This commitment should be visible in the strategic planning of the institution and messaging by academic leadership. Participants of the Robert Wood Johnson Foundation Nurse Faculty Scholars program who were surveyed about their experience as faculty described the visible commitment of their dean to DEI as integral to their success 35. Such support needs to include valuing DEI contributions, as well as valuing types of research, such as qualitative or community research, which can contribute to health equity.…”
Section: Recommendationsmentioning
confidence: 99%